Temporary contracts and monopsony power in the UK labour market - Domenico Tabasso (Institute for the Study of Labor (IZA), 2011)
This paper addresses the applicability of the theory of equalizing differences (Rosen, 1987) in a market in which temporary and permanent workers co-exist. The assumption of perfect competition in the labour market is directly questioned and a model is developed in which the labour market is described as a duopsony and the relation between wage and non-monetary job characteristics is studied for workers with different contract lengths. The empirical analysis, based on several waves of the UK Labour Force Data, confirms several of the hypotheses suggested by the model and emphasizes how in the short run workers who have experienced a change in their employer can expect a career trajectory in line with the theory on compensating differentials. In particular, while the wage dynamic related to workers shifting from a temporary contract to another temporary position cannot be exactly predicted, shifts from temporary to permanent contracts tend to be linked to a reduction in wages and a simultaneous increase in travel-to-work distance. Nonetheless, when unobserved characteristics are accounted for in the selection process into temporary contracts, these results lose significance and only a positive relation between wage and commuting time persists, irrespective of the type of contract.
urn:nbn:de:101:1-201108092947
Keywords: J22; J31; J41; J42; L13; 330; atypical contracts; oligopsony; compensating differentials; commuting time; Arbeitsmarkt; Arbeitskräfte; Leiharbeit; Arbeitsmobilität; Lohn; Großbritannien